THE EFFECTS OF INJECTING INTRA ARTICULAR PLATELET-RICH PLASMA ON PAIN SCORES IN KNEE JOINT OSTEOARTHRITIS - Ahmad, Khaleel; Ali, Liaquat; Maan, Muhammad Aasam Masoom (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the effects of intra articular platelet rich plasma (PRP) injection on level of pain of knee joint in patients with knee osteoarthritis. Study Design: Prospective observational study. Place and Duration of Study: Combined Military Hospital Rawalpindi, from Aug 2018 to Jan 2019. Methodology: Forty patients with pain due to knee osteoarthritis for intra-articular injection were included in this observational clinical trial after informed consent and fulfilling inclusion criteria. After measuring pain by numerical rating scale, patients received intra articular platelet rich plasma (10ml) therapy in affected knee under fluoroscopy. Using the Numerical rating scale level of pain was evaluated and recorded for each patient at different intervals. Results: There was dramatic improvement in pain score after first and second injection of platelet rich plasma. There was 33.33% improvement at 3rd week, 54.32% at 6th week and 71.60% at 6th month. Conclusion: Platelet rich plasma is safe, cost effective and minimally invasive in reducing pain scores and functional limitation in knee osteoarthritis.